Las rampas Carbonatadas del Triásico Medio en el sector central de la Cordillera Ibérica. - Meléndez, Alfonso; Aurell, Marcos; Bádenas, Beatriz; Soria, Ana Rosa (Cuadernos de Geología Ibérica, 1995)
Sin resumen